Characterization of emulsion stabilization properties of quince seed extract as a new source of hydrocolloid. (July 2016) - Kirtil, Emrah; Oztop, Mecit H.
Abstract: The capability of seed extracts in stabilizing emulsions has particularly received interest in recent years. Upon soaking quince seeds into water, biopolymers inside the seeds are extracted to water, forming mucilage. This study investigates the physical stability, rheology and microstructure of oil (sunflower oil) in water emulsions, stabilized by 2% (w/v) whey protein isolate with varying concentrations of xanthan and quince seed gum. Quince seed gum resulted in emulsions with smaller low-shear viscosities and shear thinning capabilities compared to the same concentrations of xanthan. Quince seed gum emulsions with concentrations ≤ 0.1 (w/v), displayed rapid creaming due to bridging flocculation. Despite the difference in apparent viscosities, for gum concentrations < 0.2 (w/v), both gums demonstrated comparable stability with xanthan gum in general yielding marginally more stable emulsions. Gum concentrations > 0.3 (w/v) resulted in physically stable emulsions even after 5 months. Overall, quince seed gum displayed significant emulsification and stabilization properties. Graphical abstract: Highlights: Quince seed gum (QSG) displayed significant emulsification properties. QSG resulted in emulsions with smaller low-shear viscosities. T2 relaxation times of QSG samples were indicative of emulsification properties. Bridging flocculation was hypothesized at lower concentrations of quince seed gum.